Model Driven Therapy - Cinquin, P.; Troccaz, J. (Methods of Information in Medicine, 2003)
Objectives: Taking into account a priori knowledge is a key issue to meet the medical, scientific and industrial challenges of the progresses of Minimally Invasive Surgery. We propose an overview of these challenges.Methods: Models play a major role in representing the relevant knowledge to plan and realize complex medical and surgical interventions. We analyze the three basic steps of Perception, Decision and Action, and illustrate by some instances how models may be integrated in these steps.Results: We propose a selection of the results obtained in Model Driven Therapy. These results illustrate the issues of Perception (models allow accurate reconstruction of 3D objects from a limited set of X-ray projections), Decision (models allow to take into account elastic and dynamic characteristics of muscles), and Action (models allow to design innovative navigational and robotics aids to the realization of complex interventions). Likewise, models play a major role in the process of surgeon’s education, which leads to the concept of Virtual Orthopedic University.Conclusions: Model Driven Therapy emerges as the way to perform optimal medical and surgical interventions, providing physicians and surgeons with the possibility to augment their capacities of sensing multi-modal information, of combining them to define optimal strategies, and of performing accurate and safe actions.
Keywords: Medical imaging; medical robotics; surgical navigation; virtual university